2018
DOI: 10.1002/cphc.201701242
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Conformation of the Bridged Monosaccharide Levoglucosan

Abstract: Levoglucosan is one of the main products of the thermal degradation of glucose and cellulose and is commonly used as a tracer for biomass burning. Herein we report a conformational analysis of levoglucosan under isolation conditions, by means of microwave spectroscopy coupled with ultrafast laser vaporization in supersonic expansions. We observed three different conformations of levoglucosan in the gas phase. They all share a common heavy atom rigid bicyclic structure. The difference between the three of them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The acyl moiety of the acyl-donor is covalently bound to the active site of the enzyme during the Comparing the obtained values, it is possible to observe that the regioselectivity of N435 is slightly influenced by the temperature and size of the alkyl chain, exhibiting a similar tendency for OH at C4 and C2 in all conditions that were explored, except for ethyl laurate ( Figure 3B, 3-Ia-50 • C), where it is possible to observe a loss of regioselectivity at higher temperatures. Different values were obtained for CaLB_epoxy and PSIM where the preference occurred for OH-C4, as can be observed for ethyl oleate ( Figure 3C, 3-Id) and ethyl laurate ( Figure 3D, 3-Ia The acyl moiety of the acyl-donor is covalently bound to the active site of the enzyme during the two transition states in the catalytic triad [24,25]. Moreover, the alcohol and the acyl binding sites are close to each other.…”
Section: Lipase-catalyzed Acylation Of 16-anhydroglucopyranosementioning
confidence: 82%
“…The acyl moiety of the acyl-donor is covalently bound to the active site of the enzyme during the Comparing the obtained values, it is possible to observe that the regioselectivity of N435 is slightly influenced by the temperature and size of the alkyl chain, exhibiting a similar tendency for OH at C4 and C2 in all conditions that were explored, except for ethyl laurate ( Figure 3B, 3-Ia-50 • C), where it is possible to observe a loss of regioselectivity at higher temperatures. Different values were obtained for CaLB_epoxy and PSIM where the preference occurred for OH-C4, as can be observed for ethyl oleate ( Figure 3C, 3-Id) and ethyl laurate ( Figure 3D, 3-Ia The acyl moiety of the acyl-donor is covalently bound to the active site of the enzyme during the two transition states in the catalytic triad [24,25]. Moreover, the alcohol and the acyl binding sites are close to each other.…”
Section: Lipase-catalyzed Acylation Of 16-anhydroglucopyranosementioning
confidence: 82%
“…It has been shown that LG predominantly adopts the inverted chair ( 1 C 4 ) ring conformations, in which the three hydroxyl groups are axial and form an intramolecular hydrogen-bonding interaction in the gas phase (38) and in crystals (39). The all-axial 1 C 4 conformation was also observed in the LG molecule bound to LGK (15).…”
Section: Reaction Mechanism and Substrate Recognition Of Lgdhmentioning
confidence: 99%
“…129 In the chair conformation, the intramolecular interactions, due to hydrogen bonding occurring between the hydroxyl of C3 in the axial position and the oxygen in C6, also in axial, contribute to a greater stabilization of the molecule, increasing its population, but decreasing its reactivity as a nucleophile. 99,130 The same interaction, hydrogen donor-acceptor, can occur with the hydroxyls in C2 and C4, according to Fig. 12A1-A3 (Fig.…”
Section: Applications Of Pure Lgmentioning
confidence: 83%